Seawater Pollution in the Arabian Gulf: Unveiling Risks and the Urgent Need for Local Standards - Sophia Ghanimeh (17787575) (2025)
Seawater is the major source of domestic water supply around the Arabian Gulf, namely the countries of the Gulf Cooperation Council. Even though these countries have significantly improved regulating and protecting seawater, they still lack comprehensive “locally adapted” standards. From this perspective, this paper documents the risk of marine pollution in the Arabian Gulf, taking Qatari seawater as a case study. The seawater was analyzed for an extensive set of compounds, including Cr, Ni, Cu, As, Cd, Pb, Ba, Be, Mn, Mo, Sb, Al, B, Co, Li, Sr, V, Ca, K, Mg, P, Na, and Fe. The risk associated with metal contamination was assessed using three indicators: Contamination Factor (CF) for the effect of individual metals, Ecological Risk Index (ERI) for the combined impact of metals, and Dermatological Chronic Daily Intake (CDIderm) for human health impact. The levels of the remaining tested components were benchmarked against seawater in other countries. Even though most metals do not pose a significant risk, Cu and Ni exhibited maximum CF values of 12 and 60, respectively, that exceed the high-risk threshold of 6. The ERI varied from no risk to considerable risk, with two samples showing elevated contamination with risk values of 15.9 and 25.3, indicating the presence of alarming polluting activities. This underscores the need for systematic monitoring, backed with fully developed seawater standards, feeding into national regulations and policy-making. This requires establishing background values that are specific to each GCC site and implementing real-time pollution tracking protocols. In addition, national pollution risk indicators shall be developed and enforced through environmental licensing and industrial discharge permitting requirements. Other Information Published in: Earth Systems and Environment License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s41748-025-00697-w